2012
DOI: 10.1097/mej.0b013e32834bfc17
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of patient control analgesia in the treatment of acute traumatic pain in the emergency department

Abstract: PCA provides more effective pain relief and patient satisfaction when compared with the conventional method of bolus intravenous injection for the relief of traumatic pain in the emergency department setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Additionally, a meta-analysis done on the same group showed that patients preferred PCADs significantly more than standard therapy [8]. Studies which have been conducted that have evaluated patient satisfaction for patients presenting to the emergency room have also shown similar results, with the overwhelming majority of studies showing a clear preference for PCADs [9,11,33,[41][42][43][44][45][46]. This is likely due to several factors including faster time to analgesia, decreased need of nursing assistance and an increased sense of autonomy and control over one's pain [44].…”
Section: Patient Autonomy and Patient Satisfactionmentioning
confidence: 92%
See 2 more Smart Citations
“…Additionally, a meta-analysis done on the same group showed that patients preferred PCADs significantly more than standard therapy [8]. Studies which have been conducted that have evaluated patient satisfaction for patients presenting to the emergency room have also shown similar results, with the overwhelming majority of studies showing a clear preference for PCADs [9,11,33,[41][42][43][44][45][46]. This is likely due to several factors including faster time to analgesia, decreased need of nursing assistance and an increased sense of autonomy and control over one's pain [44].…”
Section: Patient Autonomy and Patient Satisfactionmentioning
confidence: 92%
“…Five out of the eight studies in question have shown statistically significant results which favor PCAD use over conventional intravenous therapy. Two of the remaining studies demonstrated a downward trend which favored PCADs (although this did not reach the threshold for statistical significance) and only one study showed no difference [9,11,33,[41][42][43][44][45][46]. Unfortunately there is…”
Section: Pain Reductionmentioning
confidence: 95%
See 1 more Smart Citation
“…PCA is commonly used for acute postoperative pain, but it can also be used for the management of other types of acute pain such as in the hospital emergency department 33 . It has been documented that acute pain is not controlled adequately in the emergency care setting 34,35 . This observation of suboptimal pain management may extend to situations in which the patient requires transfer between hospitals (usually for a higher level of care) in emergency vehicles 36,37 .…”
Section: Patient-controlled Analgesia: Backgroundmentioning
confidence: 99%
“…A smaller study from Malaysia included patients presenting with pain of traumatic origin;19 96 patients in two centres were randomised to either standard care or PCA (1 mg boluses), with a significant reduction reported in pain scores in the PCA group compared to the standard care group. The same two authors reported another smaller study of 47 patients with traumatic injury 20. Patients were again randomised to receive either standard care or PCA (1 mg boluses).…”
Section: Introductionmentioning
confidence: 99%